Game controllers for older adults : experimental study on gameplay experiences and preferences - Theng, Yin-Leng (2013)
With the world population ageing, studies had shown that gameplay influence to older adults' lives. However, there were few user studies to investigate older adults' experiences and preferences with different types of game controllers. The goal of our experimental study was to compare older adults' evaluation of three popular game controllers: (i) Button Controller, (ii) Gesture Controller and (iii) Mixed Button and Gesture Controller. Our findings showed that the older participants performed best with the Mixed Controller in Nintendo Wii. However, further analysis showed Gesture Controller in Xbox Kinect was most preferred controller type, despite some older participants having problems using body movements to complete the running game.